Analysis of the dark current distribution of complementary metal-oxide-semiconductor image sensors in the presence of metal contaminants. (28th October 2020) - Polignano, M L; Russo, F; Moccia, G; Nardone, G
Abstract: We have analysed the effects of intentional metal contamination on the dark current of complementary metal-oxide-semiconductor image sensors. A few contaminants (molybdenum, tungsten, vanadium, titanium, copper) have been selected for this study, because they previously showed the most relevant impact on the dark current. The dependence of the dark current on temperature has been analysed in contaminated diodes from different regions of the dark current distribution. The generation current is always dominant in the diodes contaminated with the metals in this study, whether diodes in the peak of the distribution or in high current tails are considered. Diodes contaminated with slow diffusers never deviate from a diffusion-generation model of the current vs temperature. Copper contaminated diodes are the only example showing a limited but significant contribution approximately independent of temperature, which can be ascribed to a local tunnel current due to copper precipitates. From the point of view of dark current spectroscopy, this analysis shows that a correct identification of the dominant impurity is more easily obtained if diodes in the peak region of the dark current distribution are analysed. Indeed, in these diodes the generation current is characterized by an energy level which is a fingerprint of the dominant impurity. Vice versa, in high current diodes the dominant energy level can be different from this level, though the generation current is even more important in these diodes.